Pengaruh Prinsip-Prinsip Good Corporate Governance Terhadap Pengelolaan Anggaran pada Instansi Pemerintah (Studi Pada Dinas Pengelolaan Keuangan, Pendapatan dan Aset Kabupaten Pandeglang Provinsi Banten) - Taufan Maulamin; Agus Cholik; Eneng Tuti Alawiah (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The purpose of this study to obtain empirical evidence about the influence of the Principles of Good Corporate Governance (Transparency, Independence, Accountability, Responsibility and Fairness) against the Budget Management in Government Agencies. The research approach used in quantitative research, was descriptive and associative. The independent variables in this study is Transparency (X1), Independence (X2), Accountability (X3), Accountability (X4) and Fairness (X5). The dependent variable in this study is the Budget Management (Y). The population in this study were employees (DPKPA) Pandeglang Banten Province totaling 65 people. The sampling technique of this research by using sampling techniques saturated. Based on the analysis with the help of SPSS version 21 for windows indicate that: Transparency affects 11.6% of the Budget Management in Government Agencies. Independence affects 22.2% of Budget Management in Government Agencies. Accountability effect of 34.4% of the Budget Management in Government Agencies. Accountability effect of 22.2% of the Budget Management in Government Agencies. The Fairness affects 14.4% of the Budget Management in Government Agencies. Principles of Good Corporate Governance jointly affect 94.6% of the Budget Management in Government Agencie.